LncRNA-84277 is involved in chronic pain-related depressive behaviors through miR-128-3p/SIRT1 axis in central amygdala - Jiao, Xiaowei; Wang, Ruiyao; Ding, Xiaobao; Yan, Binbin; Lin, Yuwen; Liu, Qiang; Wu, Yuqing; Zhou, Chenghua (Frontiers in Molecular Neuroscience, 2022)
Long-term chronic pain can lead to depression. However, the mechanism underlying chronic pain-related depression remains unclear. Sirtuin 1 (SIRT1) is a nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylase (HDAC). Our previous studies have demonstrated that SIRT1 in the central nucleus of the amygdala (CeA) is involved in the development of chronic pain-related depression. In addition, increasing studies have indicated that long non-coding RNAs (lncRNAs) play a vital role in the pathogenesis of pain or depression. However, whether lncRNAs are involved in SIRT1-mediated chronic pain-related depression remains largely unknown. In this study, we identified that a novel lncRNA-84277 in CeA was the upstream molecule to regulate SIRT1 expression. Functionally, lncRNA-84277 overexpression in CeA significantly alleviated the depression-like behaviors in spared nerve injury (SNI)-induced chronic pain rats, whereas lncRNA-84277 knockdown in CeA induced the depression-like behaviors in naïve rats. Mechanically, lncRNA-84277 acted as a competing endogenous RNA (ceRNA) to upregulate SIRT1 expression by competitively sponging miR-128-3p, and therefore improved chronic pain-related depression-like behaviors. Our findings reveal the critical role of lncRNA-84277 in CeA specifically in guarding against chronic pain-related depression via a ceRNA mechanism and provide a potential therapeutic target for chronic pain-related depression.